2018
DOI: 10.3174/ajnr.a5730
|View full text |Cite
|
Sign up to set email alerts
|

Acutely Ruptured Intracranial Aneurysms Treated with Flow-Diverter Stents: A Systematic Review and Meta-Analysis

Abstract: Flow-diversion treatment of ruptured intracranial aneurysms yields a high rate of long-term angiographic occlusion with a relatively low rate of aneurysm rebleeding. However, treatment is associated with a complication rate of 18%. When coiling or microsurgical clipping are not feasible strategies, anterior circulation ruptured aneurysms can be effectively treated with a flow-diversion technique, minimizing the number of stents deployed. Given the 27% rate of complications, flow diversion for ruptured posterio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
108
2
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 120 publications
(120 citation statements)
references
References 49 publications
7
108
2
3
Order By: Relevance
“…Moreover, there was a 4% rate of symptomatic ischemic complications. Another meta-analysis has recently been performed by Cagnazzo et al [8], reporting rates of thromboembolic and hemorrhagic complications of 8% and 7%, respectively.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, there was a 4% rate of symptomatic ischemic complications. Another meta-analysis has recently been performed by Cagnazzo et al [8], reporting rates of thromboembolic and hemorrhagic complications of 8% and 7%, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Recent advances in polymer coating technology have led to FDS with reduced thrombogenicity becoming available (e.g., PED Shield; Medtronic). Maning et al [9] used the PED Shield under SAPT to treat 14 patients with aSAH and reported no difference in the rate of acute stent thrombosis, permanent morbidity, or mortality compared with the meta-analysis performed by Cagnazzo et al [8].…”
Section: Discussionmentioning
confidence: 99%
“…29,30 The same group responsible for this meta-analysis also used a similar technique to analyze multiple small retrospective series of acutely ruptured aneurysms in 2018 and reported high rates of long-term occlusion but with a complication rate of 18% in the anterior and 27% in the posterior circulation. 31 Last, a 2018 meta-analysis of distal aneurysms also suggested reasonably high rates of occlusion (70%) with marked complication rates (20%). 32 Limited studies of dissecting and fusiform aneurysms demonstrate comparable outcomes to vessel sacrifice in the long term, with potentially greater short-term complications.…”
Section: Conventional Braided Mesh Devicesmentioning
confidence: 98%
“…Безпечність та ефективність методики для нерозірваних аневризм доведено у декількох дослідженнях [5][6][7][8][9]. Основними обмеженнями використання потікскеровуючих стентів у гострий період аневризматичного внутрішньочерепного крововиливу є необхідність призначення подвійної дезагрегантної терапії та розташування аневризми у вертебробазилярному басейні через підвищення ризику ішемічних усклад-нень у віддалений період (side branch occlusion) [10].…”
Section: оригінальні дослідженняunclassified
“…метааналізи [2,10] показали, що використання потікскеровуючих стентів у гострий період крововиливу можливе, якщо стандартні методи ендоваскулярної оклюзії аневризми та мікрохірургічного кліпування неможливо застосувати або вони асоціюються з високим ризиком інтраопераційних ускладнень. За даними досліджень, ризик повторної геморагії при використанні потікскеровуючих стентів становив 4 %, а ризик усіх можливих ускладнень -18 % [10]. Повторна геморагія спостерігається при аневризмах, розмір яких перевищує 7 мм (найчастіше -2 см) [2].…”
Section: оригінальні дослідженняunclassified